Bird preferences for fruit size, but not color, vary in accordance with fruit traits along a tropical elevational gradient. Issue 2 (14th February 2023) - Hazell, Richard J.; Sam, Katerina; Sreekar, Rachakonda; Yama, Samson; Koagouw, Wulan; Stewart, Alan J. A.; Peck, Mika R.
Abstract: Birds constitute one of the most important seed dispersal agents globally, especially in the tropics. The feeding preferences of frugivorous birds are, therefore, potentially of great ecological importance. A number of laboratory‐based and observational studies have attempted to ascertain the preferences of certain bird species for certain fruit traits. However, little attention has been paid to community‐wide preferences of frugivorous birds and the impact this may have on fruit traits on a broader scale. Here, we used artificial fruits of different colors and sizes to investigate community‐wide fruit trait preferences of birds at three sites along an elevational gradient in Papua New Guinea. We recorded attack rates on artificial fruits as visible impressions made by a bird's beak during a feeding attempt. We also measured the colors and sizes of real fruits at each site, and the gape widths of frugivorous birds, allowing for comparisons between bird feeding preferences and bird and fruit traits. Regardless of elevation, red and purple fruits were universally preferred to green and attacked at similar rates to one another, despite strong elevational patterns in real fruit color. However, elevation had a significant effect on fruit size preferences. A weak, non‐significant preference for large fruits was recorded at 700 m, while medium fruits were strongly preferred at 1700 m and small fruits at 2700 m. These patterns mirror those of both real fruit size and frugivorous bird gape width along the gradient, suggesting the potential for selective pressure of birds on fruit size at different elevations. Abstract : We used artificial fruits to examine avian community‐wide feeding preferences for fruit size and colour on an elevational gradient in Papua New Guinea. We found that birds preferentially selected artificial fruits corresponding to both frugivore gape width and the size of real fruits at each elevation, indicating the potential for selective pressure of birds on fruit size. However, colour preferences of birds did not correspond to real fruit colour prevalence at different elevations.